2020
DOI: 10.3390/jcm9061911
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, Inflammation, and Vascular Calcification in Kidney Transplant Recipients: Perspectives on Long-Term Outcomes

Abstract: After decades of pioneering and improvement, kidney transplantation is now the renal replacement therapy of choice for most patients with end-stage kidney disease (ESKD). Where focus has traditionally been on surgical techniques and immunosuppressive treatment with prevention of rejection and infection in relation to short-term outcomes, nowadays, so many people are long-living with a transplanted kidney that lifestyle, including diet and exposure to toxic contaminants, also becomes of importance for the kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 180 publications
(256 reference statements)
1
10
0
Order By: Relevance
“…Although kidney transplantation aims to recover kidney function, it incompletely mitigates mechanisms of disease such as inflammation, oxidative stress and impaired metabolic homeostasis [16]. In the current study, we found that most patients had hyperuricemia, which is in line with previous studies [21,50].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although kidney transplantation aims to recover kidney function, it incompletely mitigates mechanisms of disease such as inflammation, oxidative stress and impaired metabolic homeostasis [16]. In the current study, we found that most patients had hyperuricemia, which is in line with previous studies [21,50].…”
Section: Discussionsupporting
confidence: 92%
“…Also similar to type 2 diabetes, oxidative stress and chronic low-grade inflammation have been proposed to play an important role in pathophysiological mechanisms underlying development of PTDM in KTR [13][14][15]. Although kidney transplantation aims to restore kidney function, it incompletely abolishes ongoing chronic low-grade inflammation, oxidative stress and impaired metabolic homeostasis [16]. In outpatient KTR, several factors inherent to this clinical setting, including chronic use of calcineurin inhibitors and corticosteroid therapy, and well-documented elevation of serum uric acid (SUA), contribute to perpetuate redox imbalance and low grade of systemic inflammation [16][17][18][19][20], all converging to resemblance of the type 2 diabetes milieu.…”
Section: Introductionmentioning
confidence: 99%
“…This risk reduction, pre- and post-transplantation, could be achieved by focusing on prevention of new-onset diabetes, preventive measures for mineral and bone disorders, and reduction of hyperlipidaemia and hypertension [ 34 ]. Medical strategies in line with these focus points are age-adapted immunosuppressive therapy, stringent use of statins and antihypertensive medication, and general lifestyle interventions [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of elevated neutrophil counts and low levels of lymphocytes, detected as a single comprehensive marker of inflammation can provide more information. Previous studies mentioned that treatment to reduce vascular calcification patients with renal disease may offset the excessive risk of cardiovascular disease [41,42]. NLR outperformed other white blood cells in predicting both short-and long-term mortality.…”
Section: Discussionmentioning
confidence: 99%